MENINGKATKAN HASIL BELAJAR MATERI GAYA DAN GERAK MENGGUNAKAN MODEL PROBLEM TOGETHER HORAY - Radiansyah; Alfina Nur Islami (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes the activities of educators and students and analyzes students’ learning outcomes on the material of force and motion. The study involved 32 students in class V of SDN Pekauman 1 Banjarmasin in the first semester of the academic year of 2020/2021. The study used a qualitative research approach with classroom action research (CAR) which was conducted in four stages, planning, implementation, observation, and reflection. The data were analyzed descriptive-qualitatively based on the learning outcomes of observations and tests. The results showed that the use of a combination of the problem-together-horay model and the model combination (Problem Based Learning, Numbered-Head Together, and Course Review Horay) could be implemented very well by educators. The percentage result was implemented from 80% to 95%, which was categorized as very good. The activity of students increased from 37.5% to 87.5%, which was categorized as very active. Students’ learning outcomes significantly increased from each meeting. In the first meeting, it was only 50% completed to 87.5% in the fourth meeting. Thus, the students’ learning outcomes of the force and motion material in class IV of SDN Pekauman 1 were declared successful or complete.